Analisis Khilafah dalam Pandangan Politik Ahl al Sunnah Wa al Jama’ah di Indonesia - Mahfudoh, Sitti Atiyatul; Rohmawati, Ulva Badi'; Mamlu’ah, Aya (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The concept of the caliphate has been a subject of debate regarding its definition, implementation, and relevance within the political systems of various nations, particularly in Indonesia. This issue often raises concerns that the caliphate threatens political stability and may seek to replace the existing governmental framework. To gain a deeper understanding, this study aims to analyze the concept of the caliphate from the political perspective of Ahl al Sunah wa al Jama’ah, focusing on its definition, historical development, and application. This research employs a library-based methodology, analyzing primary and secondary sources. The findings indicate that Sunni political thought outlines four essential criteria for establishing a caliphate: descent from the Quraysh tribe, allegiance (bai‘ah), the principle of shura (consultation), and justice. Sunni scholars do not prescribe a specific formal structure for a state but emphasize the importance of implementing universal values found in the Qur’an, such as trust (amanah), deliberation, justice, equality, human rights protection, peace, and welfare. The study concludes that while the caliphate system is not feasible for application in Indonesia, Islamic principles can be integrated into the existing governance system without necessitating a change in the state’s structural form